Genetic mapping revealed that the Pun2 gene in Capsicum chacoense encodes a putative aminotransferase - Yi, Shieun; Lee, Do-Gyeong; Back, Seungki; Hong, Ju-Pyo; Jang, Siyoung; Han, Koeun; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2022)
Several genes regulating capsaicinoid biosynthesis including Pun1 (also known as CS), Pun3, pAMT, and CaKR1 have been studied. However, the gene encoded by Pun2 in the non-pungent Capsicum chacoense is unknown. This study aimed to identify the Pun2 gene by genetic mapping using interspecific (C. chacoense × Capsicum annuum) and intraspecific (C. chacoense × C. chacoense) populations. QTL mapping using the interspecific F2 population revealed two major QTLs on chromosomes 3 and 9. Two bin markers within the QTL regions on two chromosomes were highly correlated with the capsaicinoid content in the interspecific population. The major QTL contained Pun2_PJ_Gibbs_3.12 on chromosome 3, the pAMT gene, indicating that the non-pungency of C. chacoense may be attributed to a mutation in the pAMT gene. Sequence analysis revealed a 7 bp nucleotide insertion in the 8th exon of pAMT of the non-pungent C. chacoense. This mutation resulted in the generation of an early stop codon, resulting in a truncated mutant lacking the PLP binding site, which is critical for pAMT enzymatic activity. This insertion co-segregated with the pungency phenotype in the intraspecific F2 population. We named this novel pAMT allele pamt11. Taken together, these data indicate that the non-pungency of C. chacoense is due to the non-functional pAMT allele, and Pun2 encodes the pAMT gene.